Decreased expression and clinical significance of miR-148a in hepatocellular carcinoma tissues - Pan, Linjiang (Eur J Med Res, 2014)
BACKGROUND: Aberrant expression of microRNA-148a (miR-148a) has been reported in several types of malignancies. However, its expression and clinicopathological significance in hepatocellular carcinoma (HCC) has not been entirely clarified. Our objective was to investigate the clinicopathological contribution of the miR-148a expression in HCC formalin-fixed paraffin-embedded (FFPE) tissues. METHODS: Eighty-nine HCC and their para-cancerous liver tissues were recruited. Total mRNA including miRNA was isolated and miR-148a expression was determined by using real time RT-qPCR. Furthermore, the relationship between the miR-148a level and clinicopathological features was explored. RESULTS: Significantly lower miR-148a expression in HCC tissues was observed than that in adjacent noncancerous hepatic tissues. miR-148a expression was also correlated to clinical TNM stage, metastasis, status of capsular infiltration and numbers of tumor nodes. CONCLUSIONS: Underexpression of miR-148a might be associated with HCC tumorigenesis and deterioration of HCC. miR-148a might act as a suppressor miRNA of HCC and it therefore has a potential role in prognosis of HCC patients.